Development of TCL FACTS (thin layer chromatography for field authentication of curcumin in turmeric supplements) Kit - Magsombol, Rianne Marie A.; Ramos, Queenie C.; Saraza, Merle Mariete G; Orejola, Joana J. (Manila Department of Science in Pharmaceutical Sciences, College of Pharmacy, University of the Philippines Manila, 2025)
Turmeric is widely known for its health benefits but is commonly adulterated. But current methods of detecting counterfeits (e.g., HPTLC) are costly and require technical expertise. Herewith, this study aims to provide a proof of concept for a simple, portable TLC kit for identifying curcumin in turmeric supplements. The study involved the development of a TLC kit method and TLC method validation in which the Rf value, spot color, and spot size were analyzed. Validation parameters include specificity, selectivity, LOD, and precision. The kit's performance was compared with the USP method, and its stability was assessed for one month. The mobile phase n-hexane:ethyl acetate (5:5) was chosen for its low cost, relatively safer profile, and effectiveness in showing curcumin at Rf value of 0.33 ± 0.03. Other optimal conditions were equilibration of mobile phase for 5 to 120 mins and sample maceration for 10 mins. The TLC method was validated to be specific, selective, and precise in terms of color, Rf value, and spot size, having a LOD of 50 μg/mL (3 mg/g turmeric). Moreover, it had similar results to the USP method, correctly detecting curcumin presence in six products and absence in one product tested. The final TLC FACTS kit was made to include 1 or 3 testing sets with 4 and 12 testing capacity, respectively. It contains a glass jar as chamber for the mobile phase, as well as reference turmeric solution, ethanol bottles, mini-spoons, and micropipette tips for sample preparation and application onto the 4 x 5 cm TLC plate. The kit was assessed to remain stable for up to 30 days at room temperature. Overall, the study demonstrated a simple and portable TLC kit for the identification of curcumin in turmeric supplements and warrant further exploration of other safe and unregulated solvents to completely separate curcuminoids.
Thesis (Bachelor of Science in Pharmaceutical Science)--University of the Philippines Manila, July 2025
Keywords: Thin layer chromatography -- Field authentication -- Curcumin -- Turmeric supplements; Dietary supplements -- Authentication -- Herbal medicine -- Philippines; Drug adulteration -- Detection -- Thin layer chromatography kits; Turmeric; curcumin; chromatography; kit; method validation